Obstacles Experienced by Students in Online Mathematics Learning in Elementary School - Tamara, Yesiska Mikaris Citra; Herman, Tatang (International Conference on Elementary Education, 2022)
Since 2020, the Indonesian government has carried out policy updates related to education in Indonesia, namely online learning caused by the COVID-19 pandemic. This study aims to describe the obstacles experienced by students in online learning of Mathematics in Elementary Schools. The method used is descriptive qualitative with a case study research design. The results showed that 100% of students in online learning Mathematics of 11 student’s responses used multimedia as their learning Mathematics media in grade 5 at one of South Bengkulu Elementary Schools which was implemented through the WhatsApp platform, google classroom and zoom. 70.9% of online learning facilities and infrastructures for mathematics are adequate, but in the learning process, only 38.63% are carried out well by students. Students who are motivated in online learning Mathematics are also low at only 47.72%. Evaluation of students’ Mathematics learning during online learning also decreased compared to offline learning. Based on the results of the study, the conclusion is that the obstacles experienced by students in the online learning process have not been implemented properly, the lack of student’s motivation for online learning Mathematics, and the decrease of evaluation results in Mathematics learning.